ANALISIS KOMPETENSI KOMUNIKASI CUSTOMER SERVICE DALAM MENINGKATKAN KEPUASAN PELAYANAN PUBLIK - Anna Yulia Wulandari (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2015)
Communication competence of customer service can improve public service satisfaction. The purpose of this research are to describe the communication competence of customer service on servicing community and create community satisfaction on Integrated Licensing Service AgencyThe method used in this research is qualitative research. On qualitative research, communication competence described through the attitude that showed by servicer and also valuation expression that showed by customer. Data collection technique that used on this research are observation, interview, and documentation. Data analysis technique used data reduction, data presentation, and conclusion.The results on this research showed that communication competence of customer servce on integrated licensing service agency Banjarbru include knowledge component, motivation, skills, and creadibulity from comunicatior. Communication competence of customer service on BP2T official Banjarbaru have fulfilled Service Operational Standar and improving public service satisfaction.